Novel strategies for development of hemorrhagic fever arenavirus live-attenuated vaccines - Martinez-Sobrido, Luis; de la Torre, Juan Carlos (Expert review of vaccines, 2016)
Introduction: Several arenaviruses, chiefly Lassa virus (LASV), cause hemorrhagic fever (HF) disease in humans and pose significant public health problems in their endemic regions. Moreover, HF arenaviruses represent credible biodefense threats. There are not FDA-approved arenavirus vaccines and current anti-arenaviral therapy is limited to an off-label use of ribavirin that is only partially effective. Areas covered: Live-attenuated vaccines (LAV) represent the most feasible approach to control HF arenaviruses within their endemic regions. Different platforms, including recombinant viral vectors expressing LASV antigens, and the use of attenuated reassortant arenaviruses, have been used to develop LAV candidates against LASV with promising results in animal models of LASV infection, but none of them has entered a clinical trial. These vaccine efforts have been the subject of recent reviews and will not be examined in this review, which is focused on new avenues for the development of safe and effective LAV to combat HF arenaviruses. Expert commentary: The development of arenavirus reverse genetics has provided investigators with a novel powerful approach to manipulate the genomes of HF arenaviruses, which has opened new avenues for the rapid development of safe and effective LAV to combat these human pathogens.